Unraveling the role of heavy metals xenobiotics in cancer: a critical review - Sourav Pal; Sayed Mohammed Firdous (Discover Oncology)
Abstract Cancer is a multifaceted disease characterized by the gradual accumulation of genetic and epigenetic alterations within cells, leading to uncontrolled cell growth and invasive behavior. The intricate interplay between environmental factors, such as exposure to carcinogens, and the molecular cascades governing cell growth, differentiation, and survival contributes to cancer’s development and progression. This review offers a comprehensive overview of key molecular targets and their roles in cancer development. Peroxisome proliferator-activated receptors are implicated in various cancers due to their role in regulating lipid metabolism, inflammation, and cell proliferation. Nuclear factor erythroid 2-related factor 2 protects cells from oxidative damage but can also promote tumor cell survival. Cytochrome P450 1B1 metabolizes exogenous and endogenous substances, and its increased expression is observed in several cancers. The constitutive androstane receptor regulates gene expression, and its dysregulation can lead to liver cancer. Transforming growth factor-beta 2 is involved in the development and progression of various cancers by dysregulating cell proliferation, differentiation, and migration. Chelation treatment has been investigated for removing heavy metals, while genetically altered immune cells show promise in treating specific cancers. Metal–organic frameworks and fibronectin targeting represent new directions in cancer treatment. While some heavy metals, such as arsenic, chromium, nickel, and cadmium, are known to have carcinogenic properties, others, like zinc, Copper, gold, bismuth, and silver, have many uses that highlight their potential as effective cancer control tactics. There are a variety of heavy metal-based technologies that show potential for improving cancer treatment methods, including targeted drug delivery, improved radiation, and diagnostic tools. Graphical Abstract